Factors Influencing COVID-19 Vaccination Intentions Among College Students: A Cross-Sectional Study in India - Jain, Lovely; Vij, Jatina; Satapathy, Prakasini; Chakrapani, Venkatesan; Patro, Binod; Kar, Sitanshu Sekhar; Singh, Ritesh; Pala, Star; Sankhe, Lalit; Modi, Bhavesh; Bali, Surya; Rustagi, Neeti; et al. (Frontiers in Public Health, 2021)
Background Students are likely to be exposed to COVID-19 due to their mobility behavior, and especially those working in healthcare sectors. The study aimed to understand their knowledge about COVID-19 and intentions to use the COVID-19 vaccine. Methods An online cross-sectional survey was carried out among students in healthcare and non-healthcare sectors to assess their intention to uptake the COVID-19 vaccine, and its associated factors. The study used a non-probability snowball sampling technique to recruit the study participants (N=655) through social media platforms and emails. Study participants were recruited across the country, including six major geographical regions in India between November 2020- January 2021 before the introduction of COVID-19 vaccine. Descriptive Statistics was used to present the socio-demographic, and vaccine related behaviors of the study participants. Key determinants that predict vaccine acceptance among students were modelled using logistic regression analysis. For each analysis, p < 0.05) was considered significant. Results A total of 655 students recruited, 323 from healthcare and 332 from non-healthcare sectors to assess their intention to uptake the COVID-19 vaccine. Of the 655 students, 63.8% expressed positive intention to uptake the vaccine. The acceptance was higher among non-healthcare students (54.07% vs 45.93%). At the time of the study 27.8% students exposed to a confirmed COVID-19 patient. 93.4% of the students had knowledge about the COVID-19 virus, and most (89.31%) of them were aware about the development of a COVID-19 vaccine. Only (33.44%) student showed concern to get infected with COVID-19 infection. Trust in the healthcare system [aOR: 4.138; 95% CI: 2.831-6.049] and trust in the domestic vaccine [aOR: 1.460; (95% CI: 1.022-2.086), p=0.038] emerged as the significant predictors of intention to uptake the vaccine among students. Students in non-healthcare sector were more willing to uptake the vaccine when available [aOR: 1.982; 95% CI: 1.334-2.946, p=0.001]. Conclusion These findings show that Indian students had positive attitudes towards the uptake of the COVID-19 vaccine, although a significant minority were not sure or unwilling to take vaccine. The lower risk perception for COVID-19 infection among students at that time could be a reason for vaccine hesitancy.